Hubungan Antara Sikap dan Dukungan Suami dengan Praktik Pemberian ASI Eksklusif pada Ibu tidak Bekerja yang mempunyai Bayi 7-12 Bulan di Wilayah Kerja Puskesmas Ngemplak SImongan Kecamatan - Yuyun Dwi Kohariningsih; Ngadiyono Ngadiyono (JURNAL KEBIDANAN, 2013)
UNICEF states in order to reduce infant mortality in Indonesia and deaths of children under five in the world each year could be prevented through exclusive breastfeeding for 6 months, in Indonesia the policy set out in the Decree of the Minister of Health No.450/Menkes/SK/IV/2004. Indonesia has a target SPM of 80% but in Central Java is still very difficult to reach that number, in Semarang coverage of exclusive breastfeeding rate in 2011 only was 21.16%, and one of them at the Ngemplak Simongan health center in 2011 E0-E6 19.20 %. The purpose of this research is "To Know the relationship between atti-tude and husband support to the practice exclusive breastfeeding in the work area clinic Ngemplak Simongan Semarang district west of the city of Semarang in 2013" In this study using a retrospective approach to correlation and Propor-tionate Stratified Random Sampling Research done in the Working Area Health Center Ngemplak Simongan Western District of Semarang. The instrument used was a questionnaire, test data analysis with continuity correction. There results of this study demonstrate the relationship between attitudes to the practice of exclusive breastfeeding with p value = 0.001 ( x2 tables = 3.841 and There is a significant relationship between husband support the practice of exclusive breastfeeding with p value = 0.007 ( x2 table = 3.841. Suggestion: need to increase information about exclusive breastfeeding through education that included her husband to be able to help mothers to breastfeed exclusively in the target scope that exclusive breastfeeding can be achieved